2020
DOI: 10.1590/1516-4446-2018-0237
|View full text |Cite
|
Sign up to set email alerts
|

Schneider’s first-rank symptoms as predictors of remission in antipsychotic-naive first-episode psychosis

Abstract: German psychiatrist Kurt Schneider proposed the concept of first-rank symptoms (FRS) of schizophrenia in 1959. However, their relevance for diagnosis and prediction of treatment response are still unclear. Most studies have investigated FRS in chronic or medicated patients. The present study sought to evaluate whether FRS predict remission, response, or improvement in functionality in antipsychotic-naive first-episode psychosis. Methods: Follow-up study of 100 patients at first episode of psychosis (FEP), with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
2
4
1
Order By: Relevance
“…This is broadly consistent with previous reports that experiencing these symptoms is predictive of negative outcomes: Stephen et al 16 found the absence of somatic passivity to correlate with better outcomes in 66% of patients; Koehler17 found no significant difference in outcomes between patients experiencing any thought interference subcomponent or somatic passivity but concluded that their absence was predictive of a better prognosis. Malinowski et al found that thought broadcasting seemed predictive of disease continuation without remission, but that this effect was no longer significant after adjusting for external factor influence (specifically, untreated psychosis duration and drug abuse)35; accordingly, although different covariates were included, our results suggest that thought broadcast does not have a significant effect on outcome. Similar prevalence and overlap between thought insertion, withdrawal and broadcasting suggests that this cannot be due to broadcasting occurring more frequently in isolation.…”
Section: Discussioncontrasting
confidence: 62%
“…This is broadly consistent with previous reports that experiencing these symptoms is predictive of negative outcomes: Stephen et al 16 found the absence of somatic passivity to correlate with better outcomes in 66% of patients; Koehler17 found no significant difference in outcomes between patients experiencing any thought interference subcomponent or somatic passivity but concluded that their absence was predictive of a better prognosis. Malinowski et al found that thought broadcasting seemed predictive of disease continuation without remission, but that this effect was no longer significant after adjusting for external factor influence (specifically, untreated psychosis duration and drug abuse)35; accordingly, although different covariates were included, our results suggest that thought broadcast does not have a significant effect on outcome. Similar prevalence and overlap between thought insertion, withdrawal and broadcasting suggests that this cannot be due to broadcasting occurring more frequently in isolation.…”
Section: Discussioncontrasting
confidence: 62%
“…Tandon et al (2013) reported that changes in the definition of criterion A symptoms had little impact on the caseness of SZ, as fewer than 2% of patients diagnosed with SZ using the DSM-IV failed to meet the DSM-5 criteria because of these changes. However, the frequency of delusional perception has been reported to be very high (77%) in antipsychotic-naïve first-episode psychosis (FEP) (Malinowski et al, 2020). If these patients had only delusional perception or any other FRSs, their diagnosis could be SZ by the DSM-IV-TR but OSSOs by the DSM-5.…”
Section: Introductionmentioning
confidence: 99%
“…For the diagnosis of schizophrenia, the use of Bleuler's 4As and Schneider's first-rank symptoms (auditory hallucinations, thought withdrawal insertion, thought interruption, thought broadcasting, somatic hallucinations, delusional perceptions, and feelings or actions as created or influenced by external agents) remains important. 12,13 Based on these conceptions, basic and clinical research have been performed to identify useful markers for diagnosis. However, no definitive physical symptoms, laboratory findings, or biomarkers reflecting pathophysiology have been found to be diagnostic.…”
Section: Symptoms and Diagnosismentioning
confidence: 99%